1139 Epidural stimulation of the ventral and dorsal cervical spinal cord. (1st December 2017) - Kersey, James; Jackson, Andrew; Baker, Mark R
Abstract : Spinal cord stimulation is a potential method for reanimating or aiding neurorehabilitation in people with spinal cord injury with restoration of use of the upper limbs consistently rated most desirable. Stimulating the epidural surface (ES) of the spinal cord is a less invasive approach than intraspinal stimulation. We stimulated the ES of the cervical cord in three anaesthetised maccaca mullata and analysed the response seen to a variety of protocols with EMG recordings from muscles of the upper limb, comparing stimulation at the ventral and dorsal surfaces. Repetitive trains of above threshold stimulation produced a consistent response when delivered to the ventral surface whereas repetitive dorsal stimulation suppressed the response after the first stimulus implying involvement of inhibitory circuits. When pairing subthreshold stimulation at the dorsal cord with weak cortical stimulation we saw facilitation of the muscle response by up to 276.21% (±17.60) compared to only 47.87% (±4.51) at the ventral surface. These results provide further support for the use of epidural stimulation in the design of future neuroprostheses. Ventral surface stimulation is better for producing consistent responses. Dorsal surface stimulation is likely to have more of a role in neurorehabilitation because of its ability to facilitate cortical input.